International Trade and Real Wages - Figueroa, Adolfo (2017)
The facts indicate that real wage rates tend to be homogenous within the First World, but they exhibit significant differences between the First World and the Third World. The standard neoclassical trade model predicts real wage equalization across countries. This prediction is consistent with the first fact, but is refuted by the second. On the other hand, the standard Ricardian model does not predict real wage equalization, so in principle these facts do not refute the model; however, it is unable to explain the wages-profits distribution. This paper proposes a generalized Ricardian trade model, which solves this theoretical difficulty. The generalized model is able to explain both facts about real wages and international trade. On epistemological grounds, the Ricardian theory proves to be superior to the neoclassical theory.